Plasticity under pressure: the influence of shear stress on larval echinoid morphogenesis - Dakin, Maggie; Patterson, Joshua; Petrosino, Alex; Smith, Jessica; Pilnick, Aaron (Frontiers in Marine Science, 2025)
IntroductionIndividuals of some marine species can modify their phenotype in response to environmental factors, allowing them to adapt to new conditions throughout their ontogeny. Echinoids represent an ecologically significant taxon that exhibit such plasticity throughout a biphasic life history in response to known biotic and abiotic factors. Preliminary lab-based observations have suggested that morphological traits, specifically pluteal arm length, may be influenced by physical processes such as hydrodynamic flow during planktotrophic larval development. This dynamic remains understudied despite potentially critical demographic implications.MethodsHere, we tested the effect of continuous exposure to different shear stress treatments on larval morphology and life history timing shifts in three co-occurring species: Lytechinus variegatus, Tripneustes ventricosus, and Diadema antillarum.ResultsBoth T. ventricosus and D. antillarum displayed significantly longer postoral arms and increased percent metamorphic competence in response to greater shear. Treatment effects were not observed for L. variegatus.DiscussionThese findings represent the first observation of morphogenic plasticity in response to a hydrodynamic factor for larval echinoderms. Species-specific effects revealed a plasticity continuum which may be mediated by phylogeny, ecological niche, and/or functional morphology. This dynamic response offers insights into larval dispersal and recruitment potential, adult distribution, and the boom-and-bust cycles characteristic of ecologically relevant echinoid populations.